Hepatoprotection of mentha aquatica L., lavandula dentata L. and leonurus cardiaca L. - Pereira, Olívia R. (2019)
The phenolic composition of hydroethanolic extracts of Mentha aquatica L., Lavandula dentata L. and Leonurus cardiaca L., obtained from plants grown under organic cultivation, was determined and their hepatoprotective effects were investigated in vitro . L. cardiaca extract was rich in phenylethenoid glycosides, especially lavandolifolioside (254 ± 36 μg/mg), whereas rosmarinic acid and eriodictyol-O-rutinoside were the major phenolic compounds of L. dentata and M. aquatica extracts, accounting for 68 ± 7 μg/mg and 145 ± 22 μg/mg, respectively. These differential phenolic components presumably account for their dissimilar antioxidant properties. While L. cardiaca extract showed moderate biological effects, M. aquatica extract displayed high antioxidant activity in chemical models, and that of L. dentata was effective in counteracting potassium dichromate-induced ROS generation in human hepatocarcinoma cells. Moreover, M. aquatica extract (50 μg/mL) and its mixture (50%/50%) with L. dentata extract displayed an effective cytoprotective effect.